Imitation – Translation – Notation: Music, Cultural Transformation and the Making of a Community in the Moravian Mission Station of Baviaanskloof/Genadendal (South Africa) - May, Jürgen (Exchange, 2025)
Using mission diaries and sheet music preserved in the Genadendal Music Archive, the article explores how Moravian music was adapted and transformed in the eighteenth- and nineteenth-century mission community of Genadendal in the South African Cape Colony. On the one hand, the article argues that Moravian practices of musical teaching and music-making in the mission of Khoisan populations must be understood as a forced cultural transfer which operated under colonial circumstances, which included claims of ‘white supremacy’. On the other hand, it documents an active role of the Khoisan in adopting Moravian music practice. Considering the example of choral singing by Khoisan children and the enduring tradition of the "Posaunenchor", the article invites the reader to consider to what extent music practised by the Genadendal community can be seen as an African music tradition.